Comparative studies on nutritional composition of captive and wild southern hake Merluccius australis broodstocks (Revista de Biología Marina y Oceanografía, 2021)
The proximal composition, amino acids and fatty acid profile were determined in whole body of wild and captive southern hake (Merluccius australis) in order to evaluate the differences in nutrients content due to the nutritional quality of the feed consumed during broodstock conditioning of this species. Body composition of southern hake did not show significant differences in dry matter, protein or ash content between both studied groups. Conversely, lipid content was significantly higher in the whole body of captive fish compared to the wild fish. In addition, the concentration of linoleic, docosahexaenoic and eicosapentaenoic acids, showed significantly higher level in captive hake than the wild hake. Amino acids concentrations did not vary between fish, except threonine and taurine. Threonine concentration was higher in wild hake whereas taurine concentration was higher in captive hake. The results of this comparative study provide a better understanding of the effects of supplemented feed currently used to acclimate and maintain in captivity southern hake broodstock.